An in-depth analysis of the operations workflow of a Bangladeshi advertising agency (Glitch DHK) - Karim, Syeda Anan (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.